2011
DOI: 10.1007/s00125-011-2141-5
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive hypoglycaemia increases serum adrenaline and induces monocyte adhesion to the endothelium in rat thoracic aorta

Abstract: Aims/hypothesis Severe hypoglycaemia associated with diabetes management is a potential risk for cardiovascular diseases. However, the effect and mechanism of hypoglycaemia on the progression of atherosclerosis remains largely unknown. As a first step towards elucidating the above, we investigated the effect of hypoglycaemia on monocyte-endothelial interaction. Methods Insulin was injected intraperitoneally once every 3 days for 5 weeks in Goto-Kakizaki rats, a non-obese rat model of type 2 diabetes. We counte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 31 publications
1
33
0
Order By: Relevance
“…Subsequent to hypoglycemia, the counter-regulatory hormonal response [51] may lead to progression of atherosclerosis, amplified platelet activation, leukocyte mobilization, and coagulation [52][53][54], which may further trigger cardiovascular disease events. Furthermore, with the increase in catecholamine release, hypoglycemia has also been associated with marked hemodynamic perturbations [18], cardiac arrhythmia [19,20], and aggravated cardiac and cerebral ischemia [22].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent to hypoglycemia, the counter-regulatory hormonal response [51] may lead to progression of atherosclerosis, amplified platelet activation, leukocyte mobilization, and coagulation [52][53][54], which may further trigger cardiovascular disease events. Furthermore, with the increase in catecholamine release, hypoglycemia has also been associated with marked hemodynamic perturbations [18], cardiac arrhythmia [19,20], and aggravated cardiac and cerebral ischemia [22].…”
Section: Discussionmentioning
confidence: 99%
“…11 The increase in catecholamine also leads to platelet activation, leucocyte mobilisation, and coagulation, 12 which may trigger cardiovascular disease events. Inflammation and endothelial dysfunction are also induced by acute hypoglycaemia, 13 and both play roles in the development of atherosclerosis. Furthermore, cardiac ischaemia or fatal arrhythmia during hypoglycaemia may lead to cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] If severe hypoglycaemia induces cardiovascular disease events, it may also dilute the potential benefit of intensive glucose control on such events because intensive glucose control increases the risk of severe hypoglycaemia. 3 This is biologically plausible because severe hypoglycaemia has acute effects on sympathoadrenal activation, 11 inflammation, 12 and endothelial function, 13 all of which have potential adverse cardiovascular effects. In addition, cardiac ischaemia or fatal arrhythmia during hypoglycaemia may be responsible for the increased risk of cardiovascular disease among patients with severe hypoglycaemia.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been suggested that the progression of macroangiopathies is related to the level of postprandial hyperglycemia and glycemic variability (5)(6)(7)(8). Repetitive hypoglycemia also had several adverse effects in the development of atherosclerosis (9). As HbA1c may not be a sensitive marker of glycemic fluctuation (10), a specific surrogate marker that better reflects glycemic variance is needed in clinical practice.…”
Section: Introductionmentioning
confidence: 99%